2021
DOI: 10.1113/jp281293
|View full text |Cite
|
Sign up to set email alerts
|

Functional reserve and sex differences during exercise to exhaustion revealed by post‐exercise ischaemia and repeated supramaximal exercise

Abstract: support-information-section). Key pointsr Females have lower fatigability than males during single limb isometric and dynamic contractions, but whether sex-differences exist during high-intensity whole-body exercise remains unknown.r This study shows that males and females respond similarly to repeated supramaximal whole-body exercise, and that at task failure a large functional reserve remains in both sexes.r Using post-exercise ischaemia with repeated exercise, we have shown that this functional reserve depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 102 publications
(304 reference statements)
1
16
0
Order By: Relevance
“…The current study findings of lower BF/VC in PMF when compared with age-matched men diverge from all aforementioned studies, but may represent a positive functional adaptation in PMF. Indeed, young PMF have reported greater intrinsic mitochondrial function (53), a phenomena that may be linked to greater oxygen extraction (54) resulting from adaptations secondary to lower oxygen carrying capacity and central blood flow limitations specific to this population. Thereby, in context of the current study, which used a small muscle mass model to assess BF and VC across absolute workloads, the lower BF response to exercise in PMF (when compared with the age-matched men) may be due to a greater oxygen extraction and utilization efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The current study findings of lower BF/VC in PMF when compared with age-matched men diverge from all aforementioned studies, but may represent a positive functional adaptation in PMF. Indeed, young PMF have reported greater intrinsic mitochondrial function (53), a phenomena that may be linked to greater oxygen extraction (54) resulting from adaptations secondary to lower oxygen carrying capacity and central blood flow limitations specific to this population. Thereby, in context of the current study, which used a small muscle mass model to assess BF and VC across absolute workloads, the lower BF response to exercise in PMF (when compared with the age-matched men) may be due to a greater oxygen extraction and utilization efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that time to exhaustion was not significantly different between VOL and EVO suggests that peripheral factors play a pivotal role in determining exercise tolerance. Moreover, because it is widely accepted that at volitional exhaustion the muscle still possesses an important functional reserve (42,43), it is reasonable to expect that our subjects did not terminate the exercise because of the muscles’ inability to perform the required work. Rather, it is more plausible that inhibitory feedback coming from group III/IV muscle afferents played an important role in exercise termination.…”
Section: Discussionmentioning
confidence: 98%
“…The apparent insensitivity of human skeletal muscle to antioxidant administration may depend on the dose and type of antioxidant, the characteristics of the subjects and type of exercise employed. Thus, a novel exercise paradigm using repeated cycles of exercise to exhaustion followed immediately by a brief occlusion of the circulation and resumption of exercise with open circulation to elicit repeated cycles of ischaemia-reperfusion has been employed to investigate mechanisms of functional reserve [ [15] , [16] , [17] , [18] , [19] ]. This protocol can be used to test whether the characteristics of the subjects and their muscle phenotype, including resting expression of Keap1 and Nrf2, could explain differences in exercise performance and metabolism in humans repeatedly exercising to exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…PCr resynthesis depends on O 2 availability [ 29 , 31 ] and no PCr recovery is observed if ischaemia is applied at exhaustion [ 15 , 32 ] or if exercise is performed during ischaemia and the occlusion remains in place until exhaustion [ 33 ]. However, we have shown that a partial recovery of exercise capacity is possible despite the application of ischaemia at the end of high-intensity exercise to exhaustion [ [15] , [16] , [17] , [18] , [19] ]. Thus, some “functional reserve” or capacity to produce power at the same level or higher than reached at exhaustion exists at task failure, which depends on the glycolytic component of substrate level phosphorylation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation